Spiritual Measures to Support Human Existence in Prison According to F. Dostoevsky's Novel: Notes from the House of the Dead - Ramonas, Arvydas (Lateranum, 2023)
The article analyses the drama of human existence experienced in prison. The main source chosen is the novel "Notes from the House of the Dead" (1861-1862) by Fyodor Mikhailovich Dostoevsky (1821-1881), a classic of Russian literature, which was written based on his personal experience as a political prisoner (1849-1859). Reflections on Christianity in the lives of prisoners and how faith helps to endure years in prison are discussed. Prayer, the reading of the Scriptures, the sharing of alms, the mercy of doctors, the perceived dignity of the image and likeness of God, the celebration of religious holidays have become religious pillars.